Psoriasis Pustulosa Generalisata: Tinjauan Kasus Pada Geriatri - Febe Sintia Kristiani; Dwi Indria Anggraini (Medula, 2020)
Psoriasis is a chronic disease of the skin that is characterized by accelerated epidermal exchange and a faster keratinization process. Psoriasis has a variety of manifestations, one of which is generalized pustular psoriasis characterized as pustular sterile eruption. This case report aims to determine the diagnosis and management of generalized pustular psoriasis. Case, a 75-year-old woman complained of the emergence of pustule throughout the body since four days ago accompanied by burning and itching sensation. Some pustule confluence make a lake form (lake of pus), and some lesion consist of erythematous plaque with yellowish greasy scale. The patient has a history of hypertension, use of pain killer, and sudden stopping steroids. Based on history taking, physical examination and laboratory, the diagnosis of generalized pustular psoriasis is made. The treatment given was in the form of corticosteroid methylprednisolone intravenous injection 31,25 mg/ 12 hours, ranitidine intravenous injection 50 mg/12 hours, cetirizine peroral 1x10 mg, betametason valerate cream 0.1% in urea 10% cream.